Reference Model for the Development of a Learning Management System with an Integrated Voice Assistant for the Optimization of the Teaching Process of a Foreign Language for People with Visual Impairment - Begazo, Mayber Javier Celis (2022)
Visually impaired people experience different accessibility barriers when they want to learn a second language through virtual classes. In addition to this, Screen Readers often have a high learning curve, plus they are not optimized for reading different languages at the same time. For this reason, it was decided to design the model of a Learning Management System (LMS) with a minimalist and accessible design and with an integrated voice assistant. As a result, it was obtained that the proposed solution was more efficient and effective in providing support to the process of teaching foreign languages in contrast to the methodology currently used.